2018
DOI: 10.1186/s12960-018-0319-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to motivation of volunteer community health workers in Ethiopia: the case of four woredas (districts) in Oromia and Tigray regions

Abstract: BackgroundThe use of community health workers (CHWs) has been considered as one of the strategies to address the growing shortage of health workers, predominantly in low-income countries. They are playing a pivotal role in lessening health disparities through improving health outcomes for underserved populations. Yet, little is known about what factors motivate and drive them to continue working as CHWs. In this study, we aimed to examine factors contributing to the motivation of volunteer CHWs (vCHWs) in Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The items were devised in multiple ways. First, a list of items was created by the investigators on the basis of previous studies on motivations for volunteering in community health programs [1420, 23, 24]. This list was then shown consecutively to two focus groups of eight volunteers each who, under the direction of one of the authors, reformulated items judged as ambiguous and suggested additional items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items were devised in multiple ways. First, a list of items was created by the investigators on the basis of previous studies on motivations for volunteering in community health programs [1420, 23, 24]. This list was then shown consecutively to two focus groups of eight volunteers each who, under the direction of one of the authors, reformulated items judged as ambiguous and suggested additional items.…”
Section: Methodsmentioning
confidence: 99%
“…Our first hypothesis, based on previous studies [1420, 23, 24], was that at least six different kinds of motives for volunteering in Ebola response programs would be found: (1) a feeling of patriotic duty, (2) a feeling of moral responsibility, (3) a desire to use one’s skills for a collective good, (4) compliance with authority, (5) a desire to gain community recognition, and (6) a seeking for personal growth. Our second hypothesis, based on the devastating consequences of Ebola in the affected poor countries in West Africa [1–3], was that the most important motives would be patriotism and feelings of moral responsibility toward fellow citizens and that the contribution of the other motives would be relatively moderate.…”
Section: Introductionmentioning
confidence: 99%
“…Such a holistic conception requires viewing supervision not just as a dyadic relationship between a supervisee and their immediate line supervisor,10–14 but rather as a system operating at several levels with a range of functions involving different actors and relationships and forms of interaction, for example, one-on-one, group and peer supervision, and so on, simultaneously 7 9. In this sense, supervision can be thought of as a set of relationships embedded in the wider context of social and professional relationships and hierarchies within the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Given the issues and challenges, some of India’s state governments started to formalize the payment to FHWs as a monthly salary rather than incentives, which is one of the most welcome steps towards improving their motivation. In addition, the intervention studies on enhancing the motivation of CHWs recommend interdisciplinary actions, such as cross-cutting approaches, training, supervision, incentives, career development, and ownership [ 52 , 53 ]. While the OH activities are drawing attention to the cross-cutting approaches with its interdisciplinary nature, these might attract the targeted FHWs in building and developing more satisfaction from their work performance.…”
Section: Discussionmentioning
confidence: 99%